Kualitas Yoghurt Susu Kambing PE Dengan Suplementasi Ekstrak Buah Lakum Terhadap Viskositas, Total Asam dan Total Padatan Terlarut - Edy Permadi; Fitri Suciati; Retno Budi Lestari (Jurnal Sains Peternakan, 2021)
This research aimed to determine viscosity, total acid, and total dissolved solid of goat milk yogurt supplemented with lakum fruit extract. This research was designed used the Completely Randomized Design (CRD) with one factor namely concentration of addition lacum fruit extract P0: 0%; P1: 0.5%; P2: 1%; P3:1.5; P4: 2%; P5: 2.5% dan P6: 3% with 3 replication. The variables observed were viscosity, total acid, and total dissolved solid. The results showed that supplementation of lakum fruit extract had a significant effect (P<0.05) on total acid value ranged between 0.88-1.44% and 0.13-0.76 dPas, but had no significant effect (P> 0.05) to total dissolved solid with a value of 15.4-21.9%. This study concludes that PE goat's milk yogurt with the addition of lakum fruit extract affected the total acid and viscosity but did not affect the total dissolved solids. Therefore, the total acid produced in this study was following SNI yogurt. Keywords: Lakum fruit extract yogurt, viscosity, total acid, total dissolved solids, goat's milk